2016
DOI: 10.1515/jas-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Croatian produced unifloral honey characterized according to the protein and proline content and enzyme activities

Abstract: A b s t r a c t In honey, the content of proteins, including the enzymes, is relatively low and has a minor nutritive significance. On the other hand, the proteins, including the enzymes, are usually used as honey quality evaluation parameters. This is because protein content and enzyme activities vary regarding the botanical origin of the honey. Since the results of protein content, glucose-oxidase, and acid phosphatase, for honeys produced in Croatia, are not available, four of the most abundant honey types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
(21 reference statements)
3
18
0
5
Order By: Relevance
“…Chestnut, lime, honeydew and mint honeys possessed statistically similar (p < 0.05) high GOX activity (341.26 ± 128.78, 350.16 ± 124.91, 376.82 ± 69.02, 402.47 ± 60.99 µg H 2 O 2 /h g, respectively), while black locust honeys approximately 10-fold lower activity (25.58 ± 21.87 µg H 2 O 2 /h g) ( Table 2). Flanjak et al (2016a) have reported similar values for the GOX activity in chestnut, honeydew and black locust honeys. Once the presence of endogenous the GOX activity in examined honeys was confirmed, the effect of honey dilution on hydrogen peroxide accumulation was investigated.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Chestnut, lime, honeydew and mint honeys possessed statistically similar (p < 0.05) high GOX activity (341.26 ± 128.78, 350.16 ± 124.91, 376.82 ± 69.02, 402.47 ± 60.99 µg H 2 O 2 /h g, respectively), while black locust honeys approximately 10-fold lower activity (25.58 ± 21.87 µg H 2 O 2 /h g) ( Table 2). Flanjak et al (2016a) have reported similar values for the GOX activity in chestnut, honeydew and black locust honeys. Once the presence of endogenous the GOX activity in examined honeys was confirmed, the effect of honey dilution on hydrogen peroxide accumulation was investigated.…”
Section: Resultsmentioning
confidence: 54%
“…Glucose oxidase activity in honey was determined by horseradish peroxidase/o-dianisidin method as previously described by Flanjak et al (2016a).…”
Section: Determination Of Glucose Oxidasementioning
confidence: 99%
“…Strelec et al [21] used 20 honey samples which were not defined as raw honey and they reached the mean of glucose oxidase values ranging from 25.58 to 402.47 μg H 2 O 2 /h·g. Also, Flanjak et al [14] observed the mean of glucose oxidase of 45 studied honey samples as 40.3-347.6 μg H 2 O 2 /h·g. According to another study, the average value of 57 blossom honey samples tagged as acacia (n � 15), wildflower (n � 32), and rapeseed (n � 8) were found as 29.7 μg/g [22].…”
Section: Glucose Oxidase Values Of Honey Samplesmentioning
confidence: 94%
“…Determination of Glucose Oxidase Activity. Glucose oxidase activity in honey was determined by the horseradish peroxidase/o-dianisidine method as previously described by Flanjak et al [14]. Glucose oxidase catalyzes the oxidation of D-glucose to D-gluconolactone and subsequent transformation to gluconic acid and hydrogen peroxide (H 2 O 2 ).…”
Section: Determination Of Invertase Activitymentioning
confidence: 99%
“…In addition, it is suggested as an indicator of adulteration of honey with sugars, because its content is lowered in sugar adulterated honeys (Bogdanov and Martin, 2002). The minimum level of 180 mg/kg for proline was internationally accepted for most of the honey types which were not adulterated (Hermosín et al, 2003), except locust honey known to possess low proline content (Flanjak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%